Web scalability for startup engineers : tips & techniques for scaling your Web application - Ejsmont, Artur (New York : McGraw-Hill Education, 2015)
"Design and build scalable web applications quickly.This is an invaluable roadmap for meeting the rapid demand to deliver scalable applications in a startup environment. With a focus on core concepts and best practices rather than on individual languages, platforms, or technologies, Web Scalability for Startup Engineers describes how infrastructure and software architecture work together to support a scalable environment.You'll learn, step by step, how scalable systems work and how to solve common challenges. Helpful diagrams are included throughout, and real-world examples illustrate the concepts presented. Even if you have limited time and resources, you can successfully develop and deliver robust, scalable web applications with help from this practical guide. Learn the key principles of good software design required for scalable systems. Build the front-end layer to sustain the highest levels of concurrency and request rates. Design and develop web services, including REST-ful APIs. Enable a horizontally scalable data layer. Implement caching best practices. Leverage asynchronous processing, messaging, and event-driven architecture. Structure, index, and store data for optimized search. Explore other aspects of scalability, such as automation, project management, and agile teams"--
"This is an invaluable roadmap for meeting the rapid demand to deliver scalable applications in a startup environment. With a focus on core concepts and best practices rather than on individual languages, platforms, or technologies, Web Scalability for Startup Engineers describes how infrastructure and software architecture work together to support a scalable environment"--
Machine generated contents note: Ch 1. Core Concepts of Scalability -- Ch 2. Principles of Good Software Design -- Ch 3. Front End Technologies -- Ch 4. Web Services -- Ch 5. The Data Layer -- Ch 6. Cache -- Ch 7. Asynchronous Processing -- Ch 8. Search Engines -- Ch 9. Other Dimensions of Consideration.
Includes bibliographical references (pages 364-377) and index.
Keywords: Computer networks -- Scalability; Web applications; Application software -- Development